Utilization of TikTok as a Learning Medium for Islamic Cultural History at MTS Muhammadiyah 17 Punggulan - Hidayah, Nurul; Jamna, Muhammad Reza; Siregar, Edy Syahputra (Yayasan Rahmat Islamiyah, 2024)
The History of Islamic Culture (SKI) is an essential part of the Islamic Education curriculum, aimed at helping students understand Islamic cultural identity and values. However, teaching SKI often faces challenges, such as a lack of resources and engaging teaching methods. Innovation through the use of social media platforms like TikTok is proposed to address these issues. TikTok, as a popular short-video-based platform, shows great potential in increasing students' interest and learning outcomes. This study explores the application of TikTok in SKI education at MTS Muhammadiyah 17 Punggulan using a descriptive qualitative approach. The results indicate that TikTok enhances student engagement and motivation, makes materials more accessible and understandable, and improves the digital competence of both students and teachers. Nonetheless, challenges such as technical limitations and the risk of non-educational content require special attention. This study recommends the development of effective content, supportive school policies, and technology training for teachers to maximize the benefits of TikTok in education.